Pengaruh Model Pembelajaran RADEC terhadap Hasil Belajar Peserta Didik pada Materi Perubahan Lingkungan, Limbah dan Daur Ulang Kelas X MA - Amalia, Ilmitul; Muh. Rapi; Syamsul, Syamsul (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
The aims of this study are: to describe the learning outcomes of students who are taught by applying the RADEC learning model to the material on environmental change, waste and recycling for class X MA Madani Pao-pao, describe the learning outcomes of students taught by applying the direct learning model to material on environmental change, waste and recycling in class X MA Madani Pao-pao, and testing the effect of applying the RADEC learning model on student learning outcomes on environmental change, waste and recycling class X MA Madani Pao-pao. This type of quasi-experimental research with nonequivalent control group design. The sample selection used purposive sampling with 30 class X MIA 1 (experimental class) and 30 students in class X MIA 2 (control class). The research results obtained by descriptive analysis and inferential analysis. Cognitive learning outcomes (post-fest) in the experimental class with a mean of 84.53 were higher than the control class with a mean of 77.47. The psychomotor learning outcomes of the experimental class with a mean of 86.39 were higher than those of the control class, namely 73.30. Hypothesis testing of cognitive and psychomotor learning results shows tcount > ttable so that it is concluded that H0 is rejected and H1 is accepted or there is an influence of the RADEC learning model on student learning outcomes in the material on environmental change, waste and recycling in class X MA Madani Pao-pao